2003
DOI: 10.1097/00001813-200301000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel with epirubicin—investigations on cardiac safety

Abstract: The aim was to evaluate clinical and subclinical cardiac toxicity of epirubicin-docetaxel (ET) combination. Breast cancer patients were given epirubicin (75 mg/m2 for 15 min), followed 1 h later by a 1-h infusion of docetaxel (75 mg/m2) q3w as first-line treatment. Cardiac function was monitored using a 24-h ambulatory electrocardiogram (ECG), left ventricular ejection fraction (LVEF), physical examination and chest radiography. The median LVEF did not decrease during the course of the treatment: median LVEF w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…A decline in HRV denotes impaired cardiac autonomic activity with sympathovagal imbalance. Consistent with previous findings that have shown damaged cardiac sympathovagal balance by anthracyclines, [29][30][31] our present study also revealed that patients in the TAU groups exhibited reduced HRV after epirubicin treatment, suggesting that epirubicin impaired cardiac ANS activity. However, this decrease was prevented in TAUYT group patients, suggesting that yoga improved the epirubicin-induced ANS dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…A decline in HRV denotes impaired cardiac autonomic activity with sympathovagal imbalance. Consistent with previous findings that have shown damaged cardiac sympathovagal balance by anthracyclines, [29][30][31] our present study also revealed that patients in the TAU groups exhibited reduced HRV after epirubicin treatment, suggesting that epirubicin impaired cardiac ANS activity. However, this decrease was prevented in TAUYT group patients, suggesting that yoga improved the epirubicin-induced ANS dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, we have reported the efficacy, toxicity and cost of treatment with the combination of epirubicin and docetaxel in metastatic breast cancer [10][11][12]. This report assessed the short-term quality of life outcome.…”
Section: Introductionmentioning
confidence: 99%
“…However, the previous study reported that the paclitaxel and doxorubicin combination had a higher incidence of cardiac failure. In this respect, it seems to be safe to use doxorubicin or EPI in combination with DTX [5,[8][9][10] . Although the number of therapy courses was small, our study showed no DTX-induced fluid retention and deformity of nails at any dose level.…”
Section: Discussionmentioning
confidence: 99%
“…Holmes et al [4] reported that sequencedependent alteration in doxorubicin clearance by paclitaxel caused increased myocardial damage. In contrast, in an anthracycline/docetaxel (DTX) combination, DTX did not appear to increase the incidence or severity of doxorubicin-associated cardiotoxitcity as compared with doxorubicin alone [5] .…”
mentioning
confidence: 91%